Da’wah Culture: The Way of Bumi Langit Institute in Popularizing Tayib Lifestyle at Imogiri Bantul - Jaya, Pajar Hatma Indra (Institut Agama Islam Negeri Madura, 2017)
This research attempts to describe the Islamic preaching way used at Bumi Langit Institute in fostering Islamic lifestyle, especially tayib food consumption pattern, so as to be accepted by the society, including non-Moslems. In order to get an answer to such issue, the researcher conducted interviews to 15 informants, observation, and documentation study. This research found that a superiority of the preaching way at Bumi Langit Institute is the ability to unite some lessons contained in the Qur’an with some current empirical realities as well as present an example of living Qur’an, starting from food to the management of agriculture which can directly be learn, practiced, enjoyed, selfie, and adopted as a lifestyle at home. Bumi Langit gives a lot of scientific surprises showing that the long-left lifestyle and the unimagineable Islamic knowledge reserve far more priceless benefits than the lifestyle that is currently upheld. In addition to logical preaching messages that could be proven by empirical data, the preaching messages delivered at Bumi Langit are also supported with other uniqueness, starting from the figures of the preachers and the establishment of Islamic preaching segmentation for young-middle class who are familiar with gadget. Copyright (c) 2017 by KARSA. All right reserved DOI: 10.19105/karsa.v25i2.1308